Antibacterial Activity Test of African Leaf Extract (Vernonia amygdalina) Against Staphylococcus aureus and Pseudomonas aeruginosa Bacteria Growth. - Trifosa Sarijowan; Widdhi Bodhi; Julianri Lebang (UNIVERSITAS SAM RATULANGI, 2022)
African leaves (Vernonia amygdalina) are known to be one part of the plant that has antibacterial activity that has the potential to be developed as a traditional medicine. This study aims to determine antibacterial activity, the effect of increasing extracts and the most effective concentration on the inhibitory power of the growth of Staphylococcus aureus and Pseudomonas aeruginosa bacteria. The antibacterial activity of african leaf ethanol extract with concentrations of 5%, 10%, 20%, 40%, 80% was tested using the disc diffusion method by observing the diameter of the inhibitory zone compared to Ciprofloxacin as a positive control and CMC as a negative control. The results of measurements of the diameter of the inhibition zone concentrations of 5% (7.0 mm), 10% (9.2 mm), 20% (11.5 mm), 40% (13.8 mm), 80% (15.7 mm) in S. aureus bacteria, 5% (8.1 mm), 10% (9.1 mm), 20% (11.6 mm), 40% (13.1 mm), 80% (15.1 mm) in P. aeruginosa bacteria have provided activity to inhibit the growth of test bacteria. The results were analyzed using One Way ANOVA and continued with the Duncan test. Research shows that the higher the concentration of the extract, the greater the diameter of the inhibitory zone of bacterial growth. An extract concentration of 80% is the most effective concentration for inhibiting S. aureus and P. aeruginosa bacteria.